Analysis of the Effect of Consumption Expenditure, Foreign Direct Investment, and Manufacturing Industry moderated by Labor force on Growth of Economy of OIC Countries during the Covid-19 Pandemic - Maulidy Albar; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Pandemi COVID-19 menyebabkan pertumbuhan ekonomi global melambat. Pertumbuhan ekonomi yang dikuru melalui GDP suatu negara dipengaruhi oleh beberapa hal. OIC merupakan organisasi negara-negara muslim didunia dimana GDP mereka juga juga terdampak secara signifikan akibat pandemi COVID-19. Penelitian ini bertujuan untuk mengobservasi pertumbuhan ekonomi negara anggota OKI yang dipengaruhi oleh variabel Industri manufaktur, Penanaman Modal Asing, dan Total konsumsi yang di moderasi oleh tenaga kerja. Penelitian ini menggunakan jenis data panel. Data diambil dengan menggunakan metode purposive sampling. Penelitian ini menggunakan sampel 10 negara aggota OKI dalam rentan tahun 2018-2020. Studi ini menggunakan teknik Random Effect Model (REM) untuk melihat pengaruh hubungan variabel independen terhadap variabel dependen secara simultan maupun parsial. Hasil menunjukkan bahwa beberapa variable independen seperti total konsumsi dan Penanaman Modal Asing mampu memberikan pengaruh signifikan untuk pertumbuhan ekonomi tanpa harus dimoderasi oleh Tenaga Kerja. Sedangkan industri manufaktur ketika dimoderasi oleh tenaga kerja, justru memberikan pengaruh yang relevan kepada pertumbuhan ekonomi di beberapa negara anggota OKI saat masa pandemi Covid-19. Maka, saran kepada pemangku kepentingan diharapkan memberikan perhatian khusus terhadap sektor industri manufaktur yang sangat banyak menyerap tenaga kerja. Untuk penelitian selanjutnya, diharapkan mampu menambah jumlah sampel data jika topik yang diambil sama dengan penelitian ini karena sampel data terbatas hanya pada negara OKI dalam penelitian ini. Kata kunci: Covid-19, Pertumbuhan Ekonomi, Penanaman Modal Asing, Tenaga Kerja, OKI.   ABSTRACT The COVID-19 pandemic has caused global economic growth to slow down. Economic growth measured through a country's GDP is influenced by several things. OIC is an organization of Muslim countries in the world where their GDP has also been significantly affected by the COVID-19 pandemic. This study aimed to observe the economic growth of OIC member countries which is influenced by the variables of the manufacturing industry, foreign investment, and total consumption which are moderated by labor. This research used panel data type. Data were taken using purposive sampling method. This study used a sample of 10 OIC member countries in the 2018-2020 vulnerable years. This study uses the Random Effect Model (REM) technique to see the effect of the relationship of the independent variable on the dependent variable simultaneously or partially. The results showed that several independent variables such as total consumption and foreign investment are able to have a significant influence on economic growth without having to be moderated by the labour force. Meanwhile, the manufacturing industry, when moderated by the labour force, actually has a relevant influence on economic growth in several OIC member countries during the Covid-19 pandemic. Therefore, suggestions to stakeholders are expected to pay special attention to the manufacturing industry sector which absorbs a lot of workers. For further research, it is expected to be able to increase the number of data samples if the topic taken is similar to this recent study because the data sample in this study is limited to only the OIC countries. Keywords: Covid-19, Economics Growth, Foreign Direct Investment, Labor Force, OIC.   REFERENCES Almosabbeh, I. A., & Almoree, M. A. (2018). The relationship between manufacturing production and economic growth in the kingdom of Saudi Arabia. Journal of Economic Studies, 45(4), 674–690. https://doi.org/10.1108/JES-02-2017-0029 Anto, M., H. (2013). Introducing an Islamic human development index (i-hdi) to measure development in oic countries. Islamic Economic Studies, Vol. 19 No.2, Life 1, 69–95. Apriyono, A., & Taman, A. (2013). Analisis overreaction pada harga saham perusahaan manufaktur di bursa efek Indonesia. Jurnal Nomina, 2(2), 76–96. https://doi.org/10.29264/jmmn.v9i1.2473 Apurv, R., & Uzma, S. H. (2021). The impact of infrastructure investment and development on economic growth on BRICS. Indian Growth and Development Review, 14(1), 122–147. https://doi.org/10.1108/IGDR-01-2020-0007 As’ari, R. (2018). Pengetahuan dan sikap masyarakat dalam melestarikan lingkungan hubungannya dengan perilaku menjaga kelestarian kawasan bukit sepuluh ribu di kota Tasikmalaya. Jurnal GeoEco, 4(1), 9–18. Auzina-Emsina, A. (2014). Labour productivity, economic growth and global competitiveness in post-crisis period. Procedia - Social and Behavioral Sciences, 156(April), 317–321. https://doi.org/10.1016/j.sbspro.2014.11.195 Barkah, T., Rusgianto, S., & Wardhana, A. (2022). Impact of agricultural land and the output of agricultural products moderated with internet users toward the total export of agricultural product in three Islamic Southeast Asian countries. Media Agribisnis, 6(1 SE - Articles). https://doi.org/10.35326/agribisnis.v6i1.2261 Boukhatem, J., & Ben Moussa, F. (2018). The effect of Islamic banks on GDP growth: some evidence from selected MENA countries. Borsa Istanbul Review, 18(3), 231–247. https://doi.org/10.1016/j.bir.2017.11.004 Cahyadin, M., & Prastity, N. (2015). The effect of foreign direct investment on economic growth in organization of Islamic conference (OIC) member countries in 2000-2013. Kajian, 20(3), 255–270. Chasanah, N., & Rusmita, S. A. (2019). Pengaruh profitabilitas terhadap harga saham dengan corporate responbility sebagai variabel moderasi (perusahaan yang terdaftar di JII dan indeks sri-kehati periode 2016-2018). Jurnal Ekonomi Syariah Teori Dan Terapan, 6(11), 2331–2346. https://doi.org/10.20473/vol6iss202011pp2331-2346 Choiriyah, E. A. N., & Auwalin, I. (2020). Pengaruh harga komoditas, kurs, inflasi, foreign direct investment (FDI), dan sumber daya manusia (SDM) terhadap perekonomian negara oki. Jurnal Ekonomi Syariah Teori Dan Terapan, 7(8), 1607-1628. https://doi.org/10.20473/vol7iss20208pp1607-1628 Cotula, L. (2021). Towards a political economy of the covid-19 crisis: Reflections on an agenda for research and action. World Development, 138, 105235. Denziana, A., Indrayenti, & Fatah, F. (2014). Corporate financial performance effects of macroeconomic factors against stock return. Akuntansi & Keuangan, 5(2), 17–40. Fadhil, M. A., & Almsafir, M. K. (2015). The Role of FDI Inflows in Economic Growth in Malaysia (Time Series: 1975-2010). Procedia Economics and Finance, 23(October 2014), 1558–1566. https://doi.org/10.1016/s2212-5671(15)00498-0 Fauziana, H., Wardhana, A. K., & Rusgianto, S. (2022). The effect of education, income, unemployment, and poverty toward the Gini ratio in member of OIC countries. Daengku: Journal of Humanities and Social Sciences Innovation, 2(2), 181–191. Febriyanti, A. R., & Shofawati, A. (2020). Pengaruh variabel internal bank dan variabel makroekonomi terhadap kinerja keuangan (studi bank umum syariah di indonesia periode 2014-2018). Jurnal Ekonomi Syariah Teori Dan Terapan, 7(8), 1538. https://doi.org/10.20473/vol7iss20208pp1538-1551 Firano, Z., & Fatine, F. A. (2020). The covid-19: Macroeconomics scenario and role of containment in Morocco. one health, 10 (July), 100152. https://doi.org/10.1016/j.onehlt.2020.100152 Ghifara, A. S., Iman, A. N., Wardhana, A. K., Rusgianto, S., & Ratnasari, R. T. (2022). The effect of economic growth, government spending, and human development index toward inequality of income distribution in the metropolitan cities in Indonesia. Daengku: Journal of Humanities and Social Sciences Innovation, 2(4), 529–536. Handriyani, R., Arwansyah, & Sahyar. (2018). Analysis effect of household consumption, investment and labor to economy growth in Sumatera Utara. Proceedings of the 3rd Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL), 209–212. Hartono, D., Yusuf, A. A., Hastuti, S. H., Saputri, N. K., & Syaifudin, N. (2021). Effect of covid-19 on energy consumption and carbon dioxide emissions in Indonesia. Sustainable Production and Consumption, 28, 391–404. https://doi.org/10.1016/j.spc.2021.06.003 Hutagaol, D. T., Tarmizi, H. B., & Daulay, M. (2019). An analysis on the influence of population growth rate, economic growth, human development index, income distribution, and unemployment rate toward poverty in all provinces in Indonesia. International Journal of Research & Review, 6(1), 101–108. Iamsiraroj, S. (2016). The foreign direct investment-economic growth nexus. International Review of Economics and Finance, 42, 116–133. https://doi.org/10.1016/j.iref.2015.10.044 Juhro, S. M., & Iyke, B. N. (2019). Consumer confidence and consumption expenditure in Indonesia. Economic Modelling, 89(2020), 367–377. https://doi.org/10.1016/j.econmod.2019.11.001 Kuvvet, E. (2021). anti-corruption courts and foreign direct investments. International Review of Economics and Finance, 72(July 2020), 573–582. https://doi.org/10.1016/j.iref.2020.12.019 Liana, L. (2009). Penggunaan MRA dengan SPSS untuk menguji pengaruh variabel moderating terhadap hubungan antara variabel independen dan variabel dependen. Jurnal Teknologi Informasi DINAMIK, 14(2), 90–97. Liu, D., Xu, C., Yu, Y., Rong, K., & Zhang, J. (2020). economic growth target, distortion of public expenditure and business cycle in china. China Economic Review, 63(October 2019), 101373. https://doi.org/10.1016/j.chieco.2019.101373 Marelli, E., & Pastore, F. (2010). Labour, productivity and growth: an introductory essay. International Journal of Manpower, 31(7), 701–712. https://doi.org/10.1108/01437721011081554 Martanti, D. M., Magdalena, F., Ariska, N. P. D., Setiyawati, N., & Rumboirusi, W. C. B. (n.d.). Dampak pandemi covid-19 terhadap tenaga kerja formal di indonesia. Populasi, 28(2), 52–69. Maryati, S., Handra, H., & Muslim, I. (2021). Penyerapan tenaga kerja dan pertumbuhan ekonomi menuju era bonus demografi di sumatra barat labor absorption and economic growth towards the demographic bonus era in West Sumatra. Jurnal Ekonomi Dan Pembangunan Indonesia, 21(1), 95–107. Meilaniwati, H., & Tannia, T. (2021). Analisis pengaruh penanaman modal asing (PMA), penanaman modal dalam negeri (PMDN), trade openness (TO) dan inflasi terhadap pertumbuhan ekonomi di ASEAN-5 tahun 2009-2018. Business Management Journal, 17(1), 89–100. https://doi.org/10.30813/bmj.v17i1.2582 Pratiwi, A. C., Wardhana, A. K., & Rusgianto, S. (2022). Application of vector error correction model on macroeconomic variables toward changes in the composite stock price index. Daengku: Journal of Humanities and Social Sciences Innovation, 2(2), 219–229. Rahman, I., Ratnasari, R. T., & Wardhana, A. K. (2022). Effect of certificate of bank Indonesia sharia and Indonesian bank seven days repository rate to inflation ratio in Indonesia during covid-19 pandemic. Economic Education and Entrepreneurship Journal, 5(1), 157–174. Rashid, N. K. A., Sulaiman, N. F. C., Anang, Z., Possumah, B. T., Muhamad, S., Sa’at, N. H., Hasan, F. A., & Wahid, H. (2021). Survey dataset on the level of sustainable consumption of Malaysian households from the perspective of income and consumption expenditure. Data in Brief, 35, 106743. https://doi.org/10.1016/j.dib.2021.106743 Ridzuan, A. R., Khalid, M. W., Zarin, N. I., Ridzuan, A. R., Ismail, I., & Norizan, N. (2018). The impact of foreign direct investment, domestic investment, trade openness and population on economic growth: evidence from asean-5 countries. International Journal of Academic Research in Business and Social Sciences, 8(1), 128–143. https://doi.org/10.6007/ijarbss/v8-i1/3799 Setiawati. (2021). Analisis pengaruh kebijakan deviden terhadap nilai perusahaan pada perusahaan farmasi di BEI. Jurnal Inovasi Penelitian, 1(8), 1581–1590. Tesfay, Y. Y. (2016). Modified,l panel data regression model and its applications to the airline industry: modeling the load factor of europe north and europe mid atlantic flights. Journal of Traffic and Transportation Engineering (English Edition), 3(4), 283–295. https://doi.org/10.1016/j.jtte.2016.01.006 Usmadi. (2020). Pengujian persyaratan analisis (uji homogenitas dan uji normalitas). Inovasi Pendidikan, 7(1), 50–62. Wardhana, A. K. (2021a). the application of waqf and endowment fund based on the principles in the sharia maqashid pillar society. Prosperity: Journal of Society and Empowerment, 1(2), 107–119. https://doi.org/10.21580/prosperity.2021.1.2.8829 Wardhana, A. K. (2021b). the impact of the pro and cons policies in the jokowi era’s on the macro economy of society. Jurnal Ekonomi Dan Bisnis Airlangga, 31(2), 124–136. https://doi.org/https://doi.org/10.20473/jeba.V31I22021.124-136 Yıldırım, D. Ç., & Akinci, H. (2020). the dynamic relationships between the female labour force and economic growth. Journal of Economic Studies, 1970. https://doi.org/10.1108/JES-05-2020-0227 Zeytoonnejad Mousavian, S. R., Mirdamadi, S. M., Farajallah Hosseini, S. J., & Omidi NajafAbadi, M. (2021). determinants of foreign direct investment inflow to the agricultural sector: a panel-data analysis. Journal of Economic and Administrative Sciences, (ahead-of-print). https://doi.org/10.1108/jeas-11-2020-0196